[LB.03.11] DETRIMENTAL EFFECT ASSOCIATED WITH THE USE OF MORE THAN THREE DRUG CLASSES TO ACHIEVE BLOOD PRESSURE CONTROL IN SPRINT. (September 2017) - McCallum, L.; Llano, A.; Aman, A.; Mcclure, J.; Jardine, A.; Dominiczak, A.F.; Chowienczyk, P.; Padmanabhan, S.
Abstract : Objective: In the SPRINT trial, achievement of target BP in the intensive arm required a higher number of drugs. Whilst intensive treatment of SBP was associated with an increased incidence of adverse events, it is unclear whether the use of multiple drug classes would result in adverse outcomes. Design and method: The number of drug classes prescribed at randomisation and at 1, 2, 3, 6, 9, 12 months were used to identify distinct trajectory groups in the standard and intensive arm using Latent Class Mixed Modelling. Data were available in 8, 449 participants. Cox proportional hazard models, adjusted for age, sex, SBP (AUC 0–12 months), prevalent CVD, prevalent CKD and number of drug classes at randomisation, were used to assess the association between drug class trajectories and pre-specified outcomes from SPRINT. Results: The SPRINT population classified into 6 groups (3 standard[Std], 3 intensive[Int]) based on the trajectories of drug classes prescribed over the first year are shown in Panel A with corresponding SBP by drug class groups in Panel B. Each group is described by the number of drug classes and [AUC-SBP+/−SD mmHg] in the first year: Std-1=1.5, [134.2 ± 7.7]; Std-2 = decrease-to-1.5, [131.2 ± 7.1]; Std-3 = 3.2, [137.8 ± 8.2]; Int-4 = 2.5, [122.7 ± 8.4]; Int-5 = 4, [125.1 ± 10]; Int-6 = increase-to-4, [131.6 ± 10.1]. Int-4(n = 3924) and Int-5(n = 530), achieved SBP<125 mmHg at 12 months requiring 2.5 and 4 drug classes respectively whilst Std-1(n = 3466) and Std-3(n = 866) required 1.5 and 3.2 drug classes respectively to achieve SBP 135–140 mmHg. Std-2(n = 225) and Int-6(n = 131) showed marked changes in drug classes used over the first year. Cox proportional hazards model (reference category: Int-4, SBP <125 on 2.5 drug classes) showed Std-3(137.8 on 3.2 drug classes) and Int-5(125 on 4 drug classes) had significantly higher risk of the primary outcome, heart failure, CVD death and all-cause death (Panel C). Figure. No caption available. Conclusions: Within SPRINT, treatment with >3 antihypertensive drug classes was associated with overall poor outcomes, specifically increased risk of death and heart failure, independent of blood pressure achieved in the first year, possibly related to the period of drug exposure. These results caution clinicians to assess need for multiple drugs and tighter blood pressure control on an individual patient basis.